Antioxidant Effect of Cinnamon Bark Extract following an Exhaustive Exercise in Male Rats - Dehghan Gh, Ebrahimi S, Shaghaghi M, Jafari A, Mohammadi M, Badalzadeh R, Fallah S (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: The beneficial effects of regular exercise in preventing and treating many chronic diseases are known. Considering that the beneficial effects are lost with exhaustion, the purpose of this study was to determine the antioxidative effects of cinnamon bark extract (CBE) supplementation in attenuating markers of oxidative stress induced by an exhaustive exercise in male rats.METHODS: Eighteen male rats (200-300gr) were randomly assigned to: (control group) without treatment (exhaustive exercise group) the rats run on a treadmill to exhaustion in the last session and (supplemented group) the rats supplemented with 200 mg/kg/day of CBE for 10 weeks and run on a treadmill to exhaustion in the last session. After exhaustion of rats, blood samples were collected, then total antioxidant capacity (TAC) was measured by FRAP (Ferric Reducing Ability of Plasma) method, plasma thiol concentration and level of malondialdehyde (MDA) were measured in the serum samples by a colorimetric method (Hu) and by TBARS (Thiobarbituric Acid Reactive Substances) method respectively. GPX activity was determined using washed red cell based on Paglia and Valentine method by GPX kit.FINDINGS: Compared to control group (62.01±12.7) activity of GPX in exhaustive group (91.95±18.58) was increased (p<0.05). Compared to exhaustive exercise (2.09±0.26), significant decrease in serum level of MDA in supplemented group (1.20±0.24) and control group (1.25±0.17) was observed (p<0.01). The decrease of plasma thiol concentration in exhaustive group (0.054±0.002) ratio of supplemented group (0.18±0.04), (p<0.01) and control group (0.14±0.03), (p<0.05) was significant. Compared to control group (0.31±0.05), the significant elevation of serum TAC in supplemented group (0.55±0.08) was observed (p< 0.01).CONCLUSION: According to results of current study, CBE supplementation before an exhaustive exercise decreased lipid peroxidation and improved anti-oxidative potential in rats.